Analisis Prosedur Pelaksanaan Pengadaan Langsung Barang dan Jasa di PT. PLN Nusantara Power Services - Sven Inggil Anugerah Kretarto; R. Yuniardi Rusdianto (Student Research Journal, 2024)
This research examines the procedures for direct procurement of goods and services at PT. PLN Nusantara Power Services. Using field research method with a qualitative approach, the research was conducted through a Regular Internship program at the Head Office of PLN Nusantara Power Services Sidoarjo. The research results show that the procurement business process involves several main divisions, particularly the Operation & Maintenance division as the user and the Supply Chain Management division as the executor. There are four main methods in procurement implementation, namely; Direct Procurement, Limited Tender, Open Tender, and Direct Appointment. Direct Procurement becomes the most efficient method for small-value and low-risk procurement. The research recommends implementing advanced technological systems to optimize the procurement process and expanding vendor networks to increase the effectiveness of the company's procurement of goods and services.